2012
DOI: 10.1080/17489725.2012.682098
|View full text |Cite
|
Sign up to set email alerts
|

O brother, where art thou located?: raising awareness of variability in location tracking for users of location-based pervasive applications

Abstract: There is a diversity of ways to determine a user's location in a pervasive environment today. On a large-scale, this diversity often results in variability of location tracking conditions throughout the environment. For an important class of pervasive applications, which often rely on the ubiquitous availability of location tracking -location-based pervasive applications, the consistency of their behaviour under this variability cannot be guaranteed. This type of limitation raises a need for the adaptation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Application level adaptation : In addition to improving positional information using the approaches outlined above, it is also possible to deal with quality at the application level as a third strategy. For example, in the case of pedestrian navigation systems, it has been shown that conveying uncertainty in location information is beneficial to users [ 104 ]. Therefore, navigation systems usually use a visualization to communicate the quality of location information as a means of dealing with location uncertainty.…”
Section: Coping With Variations In the Quality Of Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Application level adaptation : In addition to improving positional information using the approaches outlined above, it is also possible to deal with quality at the application level as a third strategy. For example, in the case of pedestrian navigation systems, it has been shown that conveying uncertainty in location information is beneficial to users [ 104 ]. Therefore, navigation systems usually use a visualization to communicate the quality of location information as a means of dealing with location uncertainty.…”
Section: Coping With Variations In the Quality Of Locationmentioning
confidence: 99%
“…These visualizations could be a ’bar of connectivity’ [ 4 ] to indicate the reception of location information or a ’location status window’ to show the last known location as well as the time in minutes that has elapsed since it was last measured [ 4 ]. The most common visualization method is a circular buffer around the approximate location whose size increases with decreasing quality of location information [ 8 , 104 , 105 ]. Another application level adaptation strategy used by navigation system is to start an interactive dialogue with the user to improve the quality of location information based on their answers [ 106 ].…”
Section: Coping With Variations In the Quality Of Locationmentioning
confidence: 99%